Abordagem histórica da física moderna e contemporânea no ensino médio - Santos, Ana Cácia (2017)
This work intended to investigate on the introduction of Modern and Contemporary Physics in High School through a historical approach of Physics, based on researches and reflections. It was investigated if would be possible to teach this new Physics in the first grade of High School. The research was carried out with high school students from two state colleges in the State of Sergipe, one being in the capital and the other in the countryside. The methodology was based on action research, considering the ideas of Barbier (2007) and Franco (2005). For the data analysis, we used the Theory of Critical Thinking from the studies of Ennis (1985), Buiegon and Tarouco (2015) and Tenreiro-Vieira and Vieira (2006). In the activity developed, the students were motivated and mobilized to reflect, question and argue about the history of Albert Einstein. The results showed that it is feasible to use the historical approach in the classroom to stimulate students to study the contents of physics, as well as to work with the theme of modern physics in high school from its historical context.